The use of nanocrystalline cellulose for the binding and controlled release of drugs - John K Jackson (Dove Medical Press, 2011)
John K Jackson1, Kevin Letchford1, Benjamin Z Wasserman1, Lucy Ye1, Wadood Y Hamad2, Helen M Burt11Faculty of Pharmaceutical Sciences, University of British Columbia, 2146 East Mall, Vancouver, BC, Canada; 2FPInnovations, 3800 Wesbrook Mall, Vancouver, BC, CanadaAbstract: The objective of this work was to investigate the use of nanocrystalline cellulose (NCC) as a drug delivery excipient. NCC crystallites, prepared by an acid hydrolysis method, were shown to have nanoscopic dimensions and exhibit a high degree of crystallinity. These crystallites bound significant quantities of the water soluble, ionizable drugs tetratcycline and doxorubicin, which were released rapidly over a 1-day period. Cetyl trimethylammonium bromide (CTAB) was bound to the surface of NCC and increased the zeta potential in a concentration-dependent manner from -55 to 0 mV. NCC crystallites with CTAB-modified surfaces bound significant quantities of the hydrophobic anticancer drugs docetaxel, paclitaxel, and etoposide. These drugs were released in a controlled manner over a 2-day period. The NCC-CTAB complexes were found to bind to KU-7 cells, and evidence of cellular uptake was observed.Keywords: drug delivery, nanocrystalline cellulose, controlled release